Paradoxical cognitive reserve: Cognitive trajectories from earlier to later adulthood: Developing topics. (7th December 2020) - Eglit, Graham M.L.; Elman, Jeremy A; Panizzon, Matthew S.; Sanderson‐Cimino, Mark E.; Williams, McKenna E.; Dale, Anders M.; Eyler, Lisa T.; Fennema‐Notestine, Christine; Gillespie, Nathan A.; Gustavson, Daniel E.; Hatton, Sean N.; Hauger, Richard L.; et al.
Abstract: Background: Longitudinal studies of aging are central to identifying early predictors of and mechanisms underlying late‐life cognitive decline and dementia. However, these studies typically lack cognitive data from earlier ages. It is therefore unclear how peak young adult general cognitive ability (GCA) and maintenance of GCA from young adulthood impact subsequent cognitive trajectories. To further understand GCA change from young adulthood, we evaluated whether poor GCA maintenance coincided with accelerated brain aging and was associated with key contributors to cognitive decline in later life, namely, aggregate vascular risk and Alzheimer's disease polygenic risk (AD‐PRS). Method: In the Vietnam Era Twin Study of Aging (VETSA), 1173 individuals were administered the same measure of GCA at average age 20 and at three VETSA waves beginning at average age 56. GCA maintenance scores were created by residualizing VETSA baseline GCA on age 20 GCA. Thus, good GCA maintenance was based on observed relative to expected scores. VETSA baseline GCA and GCA maintenance scores were entered into mixed effects models to predict specific cognitive abilities across three VETSA waves (∼6 years apart). Associations between GCA maintenance scores and indices of accelerated brain aging, aggregate vascular risk, and AD‐PRS were evaluated. Result: Better GCA maintenance was associated with better VETSA baseline memory, semantic fluency, general fluency, processing speed, executive function, and working memory. However, given equivalent age 56 GCA, those who declined in GCA from age 20 outperformed those with stable GCA in memory, verbal fluency, executive function, and working memory at age 56. Thus, despite poor cognitive maintenance, some element of high peak cognitive reserve in early adulthood still confers benefit. All specific cognitive abilities declined over time, but neither VETSA baseline GCA nor GCA maintenance predicted extent of decline. Poor GCA maintenance from young adulthood was associated with accelerated brain aging and aggregate vascular risk, but not AD‐PRS. Conclusion: Both peak young adult GCA and GCA maintenance are important contributors to late midlife cognitive ability. Poor maintenance of GCA from young adulthood being associated with worse vascular health and coinciding with accelerated brain aging argues against a simple regression to the mean explanation.